The taste for the other : the social and ethical thought of C. S. Lewis - Meilaender, Gilbert, 1946- (Eerdmans, 1978)
"... Professor Meilaender portrays Lewis' vision of community and his understanding of love, its guiding principle. Lewis' attitude toward Creation is explored, as well as his thoughts on morality, pride, and the Christian journey toward fellowship with God. What emerges is a sustained vision of man in society as seen by one of the twentieth century's most articulate and influential Christians." - from publisher's description.